Optimal allocation of thermal generating units through shuffled frog leaping algorithm / Amirul Hakim Mohd Jamil - Mohd Jamil, Amirul Hakim (2016)
This thesis presents the solution of economic load dispatch problem with valvepoint effect using Shuffled Frog Leaping Algorithm (SFLA). Three and six generator systems are used to test the effectiveness of the proposed method. Sum of the optimal values of power for each generator is able to fulfill the power demand and minimize the operating cost compared to the Particle Swarm Optimization (PSO) method. The proposed algorithm is developed using MATLAB programming.